The Computational Study of Epoxy-based Nanocomposites Electromechanical Performance under External Force: Molecular Dynamics Approach - Torkian, Peyman; Baseri, Hamid (Journal of Composites and Compounds, 2024)
Gauge factor is a measure of the sensitivity of a material's electrical performance to mechanical strain. This property of nanocomposites is important for their usage in various electromechanical applications. In current research, we introduce the electromechanical and gauge factor evolutions of epoxy-graphite/boron nitride (BN) nanocomposites. The molecular dynamics (MD) approach implemented for numerical analyzing of various modeled systems. Computationally, the atomic interactions between particles inside structures described by UFF, and TERSOFF force-fields. After MD simulation settings done, various physical parameters such as temperature, potential energy, interaction energy and gauge factor reported to describe atomic behavior of designed nanocomposites. MD results predicted the physical stability of modeled systems at 300 K as initial temperature (after 10 ns). Also, gauge factor of nanocomposites converged to 3.19 and 6.54 values by graphite and BN inserting to base matrix, respectively. These results indicated by changes nanoparticles type inside epoxy-based nanocomposites, the electromechanical performance of them can be manipulated in actual cases.